Guarantee of human rights and the process of resocialization in the prison system (Research, Society and Development, 2022)
The numbers of incarceration in Brazil are worrying because of the excessive increase in the prison population, as Brazil currently experiences a situation of abandonment in the prison system. In this way, what should be an instrument of resocialization, often works as a school of crime, due to the way it is treated mainly by the State, the precarious conditions of prisons are unable to resocialize. The present study is based on the analysis of the reality of the prisoner in the Prison System and aims to analyze the responsibility of the State and society in relation to the current situation in which the prison population in Brazil finds itself, with regard to human rights, and guarantees of rehabilitation in prison. In this sense, the methodology was used to carry out the research, using the inductive approach method, and methods of scientific procedure, qualitative observational history, the observational historical procedure was done through the analysis of legal texts, and for the qualitative ones were used in the data of the Integrated Penitentiary Information System, Infopen (2017). It is concluded that the application of Human Rights in the prison system and the guarantee of resocializing processes are essential for Brazilian society. Therefore, it is relevant to broaden the discussions in its many spheres, be they governmental, social, university and in the media.